(untitled) (Praxis Educativa, 2025)
The dynamism in migratory movements with a significant participation of young people who move for reasons of study, is a phenomenon that is circumscribed within the most far-reaching cultural trends, whose influence covers not only young people from developed countries, but also from developing countries by individual and institutional factors, whose decision is determined based on the ability to cover costs and the relative quality of education in the chosen country. The objective of this research was to know the factors that influence foreign students to decide to study at the UAZ. The qualitative approach was used, a case study, applying the semi-structured interview to five foreign students from the UAZ areas and/or programs that have received a greater number of students from other nationalities. The results show that educational quality, costs, as well as the existence of links or support networks, are factors that influence foreign young people to choose UAZ with an educational alternative. It is concluded that foreign students are young people who are motivated by educational quality, costs and the networks that have been created among family, friends and acquaintances, which allow the exchange of information and support.